Activity of Superoxide Dismutase Mimic of [Mn(salen)OAc] Complex Compound Non-enzymatically in Vitro Through Riboflavin Photoreduction - Djulia Onggo; Irma Mulyani; Iwan Hastiawan; Dikdik Kurnia; Yusi Deawati (Universitas Jenderal Soedirman, 2017)
The complex compound of [Mn(salen)OAc] can serve as mSOD and its activity has been determined non-enzymatically in vitro through riboflavin photoreduction. The complex was synthesized from Mn(OAc)2.4H2O and H2salen. Based on the elemental analysis, the C=56.69%; H=4.21%; and N=7.52% content are corresponding to the chemical formula of MnC18H17N2O4. The functional groups and ionic species in the complex have been analyzed by infrared spectroscopy and ESI-MS. SOD activity was determined by mixing complex at various concentrations with riboflavin and nitroblue tetrazolium (NBT), then the mixture was lighted with 20 Watt tungsten lamp for 15 minutes in a closed box. Then the reduced NBT absorptions were measured at Î» 560 nm. The difference of absorbance between standard and sample solutions (without and with riboflavin, respectively) was multiplied by 100% to obtain %inhibition of each various sample concentration against NBT. SOD activity was obtained from IC50 data defined as a 50% inhibition of the plot curve of % inhibition to the concentration of the complex. The result obtained for this compound is IC50 = 2.7 Â± 0.05 ÂµM as well as enzymatic method. Therefore, this method can be used to determine the SOD activity by giving more stability and accuracy of IC50 value.